The Effect of Mahogany Leaf Litter (Swietenia Mahagoni (L.) Jacq.) on The Quality of Organic Fertilizer Through Vermicomposting - Wilda, Nur; Mudakir, Imam; Asyiah, Iis Nur (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Mahogany leaf litter (Swietenia mahagoni (L.) Jacq.) has high levels of lignin and C/N ratio, sothe decomposition speed is longer and can cause accumulation of litter waste. The purpose of this research was to determine the effect of applying different amounts of mahogany (Swietenia mahagoni (L.) Jacq.) leaf litter on the quality of organic fertilizer through vermicomposting. This study used acompletely randomized design (CRD) with the amount of mahogany leaf litter in each treatment was 0 g, 100 g, and200 g. Vermicomposting was carried out for 4 weeks, then the results were compared with SNI 7763:2018 and analyzed using LSD. The results showed that the addition of different amounts of mahogany leaf litter had nosignificant effect on the levels of total-N, P2O5 , C-organic, and C/N ratio but had a significant effect on the levels of K2O, and weight produced through vermicomposting. The p3 treatment with a total of 200 gof mahogany leaf litter was the most significant composition in meeting the chemical and physical quality parameters of vermicompost. This is due to the ideal balance of the C/N ratio in the material, so that vermicomposting runs optimally.